Value basics of musical enlightenment (on the example of Eastern Galicia in the first half of the 20th century) - Iryna Bermes (Maria Curie-Skłodowska University, Lublin, Poland, 2018)
The origins of musical education are rooted in the knowledge of beneficial influence of music on the human soul and its significant educational effect. Musical education can be regarded as an activity that ensures the development of musical interests, needs and tastes, and generally promotes the formation of the foundations of music. Education based on musical information is important for the individual musical development, for raising of one's cultural level. Educational idea mostly comes down to ensuring wide access to genuine musical values. As an activity, music education is closely linked with issues of training and schooling. Its main task is to involve different social groups into musical life, introducing them to the various musical sources ‒ folk songs, examples of national and world musical heritage, sharing knowledge about music. Since music is correlated with artistic images, appealing to the feelings of people, it can contribute to their spiritual purification. Specificity of musical education is in organizing prolonged and frequent contacts of listeners with music, in a voluntary initiative of performers and listeners in the quest for self education. One of the main "consumers" of musical information, the target of musical education is a listener. An important factor in the cultural development of Ukrainian East Galicia in the first third of the 20th century were the ensembles connected with community organizations such as "Prosvita", "Bojan", "Ridna Shkola", "Plast", "Sich" and others. Their participants were amateurs, the most active forces of the area that supported the traditions of Ukrainian national identity and cultural progress. Musical educational movement concentrated in choirs, orchestras, theater circles at various community organizations, each of which occupies a niche in the cultural space of Eastern Galicia.